Performance Audit of National Programme for Control of Blindness in Assam (1996-2001) - CAG of India (CAG of India, 2002)
National Blindness Control Programme (NBCP) a Centrally Sponsored Scheme was launched in Assam in 1978 to prevent and reduce the incidence of blindness amongst visually impaired and other vulnerable groups of population. A review of the programme through test-check of records indicated that funds were diverted for payment of salary and other purposes and had not been utilised for the earmarked programme activities. Low performance of cataract operations, lack of infrastructure in PHCs/CHCs/Hospitals, non-imparting of training, absence of motivation, counselling and spread of information, lack of proper planning and monitoring and poor financial discipline were the other main reasons for which the programme could not achieve any significant reduction of blindness. Following are some main audit findings: 1. Central grant of Rs.1.57 crore out of Rs. 1.59 crore remained unutilised during 1996-97 to 2000-2001 besides non-utilisation of Rs. 86.57 lakh out of the grants of Rs. 1.57 crore released by Government of India during 1992-93 to 1995-96. 2. Funds provided during 1996-2001 by Government of India for development of district hospitals, PHCs, Mobile Ophthalmic Units and construction of eye wards (Rs.16 lakh), operation theatres (Rs. 60 lakh) in the districts, IEC (Rs. 19 lakh); Renovations and Furnishing (Rs. 18 lakh) were not utilised for the purpose. 3. Records showing number of cases where vision was restored/not restored after surgery, screening of patients for refractive errors, provision for spectacles and rehabilitation of incurably blind were not maintained.
For the Period 1996-97 to 2000-01